Is Hygiene Still the Backbone of Your Practice? - Rachel Wall (Taylor & Francis Group, 2023)
ABSTRACTMaintaining a thriving hygiene department can be increasingly difficult in a world of reimbursement and staffing challenges, but a successful hygiene department is still possible. Some dental practices are retaining their hygienists, delivering outstanding patient care and hitting their revenue goals. Challenging times and external factors require business owners to fortify the basic business principles of leadership, systems, culture, team training and customer service. Practice owners who collaborate with their team and expert advisors are generating creative solutions to overcome some of the obstacles the dental profession is experiencing. This article will examine those theories and explain specific action steps for shoring up basic elements of a successful hygiene team that will lead to a successful practice.